HST imaging of redshift z>0.5 7C and 3C Quasars - Serjeant, S; Rawlings, S; Lacy, M (1997)
We present preliminary results from HST imaging of radio-loud quasar hosts, covering a ~x100 range in radio luminosity but in a narrow redshift range (0.5 to 0.65). The sample was selected from our new, spectroscopically complete 7C survey and the 3CRR catalogue. Despite the very large radio luminosity range, the host luminosities are only weakly correlated (if at all) with radio power, perhaps reflecting a predominance of purely central engine processes in the formation of radio jets, and hence perhaps also in the radio-loud/-quiet dichotomy at these redshifts. The results also contradict naive expectations from several quasar formation theories, but the host magnitudes support radio-loud Unified Schemes.